2015
DOI: 10.1016/j.ijmachtools.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Diamond machining of silicon: A review of advances in molecular dynamics simulation

Abstract: Molecular Dynamics (MD) simulation has enhanced our understanding about ductile-regime machining of brittle materials such as silicon and germanium. In particular, MD simulation has helped understand the occurrence of brittle-ductile transition due to the high-pressure phase transformation (HPPT), which induces Herzfeld-Mott transition. In this paper, relevant MD simulation studies in conjunction with experimental studies are reviewed with a focus on (i) The importance of machining variables: undeformed chip t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
111
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 345 publications
(118 citation statements)
references
References 222 publications
(232 reference statements)
2
111
0
1
Order By: Relevance
“…MD simulation demonstrated that the amorphous phase transformation in cutting of silicon is a key mechanism for inelastic deformation, and crack propagation can be avoided by stable shearing under a compressive stress [90]. MD simulations show that the high-pressure phase transformation (HPPT) of silicon results in a metallization to form a metastable phase, which persists only when the cutting tool is able to retain sufficient stress [91]. However, currently MD simulations suffer from the spurious effects of high cutting speeds and the accuracy of the simulation results has yet to be fully explored [91].…”
Section: Molecular Dynamic Simulationmentioning
confidence: 99%
“…MD simulation demonstrated that the amorphous phase transformation in cutting of silicon is a key mechanism for inelastic deformation, and crack propagation can be avoided by stable shearing under a compressive stress [90]. MD simulations show that the high-pressure phase transformation (HPPT) of silicon results in a metallization to form a metastable phase, which persists only when the cutting tool is able to retain sufficient stress [91]. However, currently MD simulations suffer from the spurious effects of high cutting speeds and the accuracy of the simulation results has yet to be fully explored [91].…”
Section: Molecular Dynamic Simulationmentioning
confidence: 99%
“…Silicon has been used extensively in both single crystal as well as in polycrystalline form for a wide range of microelectronic applications including solar cells and conducting gates for CMOS and MOSFET processing devices [1]. Recent technological trends have also led to the synthesis of nanospheres and nanowires of silicon, which would potentially provide an even broader range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the existing research details several aspects of silicon, but this material is so versatile that many new phenomena are still being explored to bridge the missing gaps in our existing understanding. Across a number of those research studies, ductility in silicon by large has been attributed either to the occurrence of high pressure phase transformation (HPPT) [1], crystal twinning [2] or surface nucleation of dislocations [3,4]. It is understood that the nucleation of dislocations is more prevalent than HPPT in the presence of free surfaces, for examples in, nanoparticles of silicon [5] while no evidence of crystal twinning during contact loading of silicon has been reported in the literature other than the work of Mylvaganam et al [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations